Preserved cutaneous silent period in cervical root avulsion - Vasko, Peter; Bocek, Vaclav; Mencl, Libor; Haninec, Pavel; Stetkarova, Ivana (The journal of spinal cord medicine, 2017)
OBJECTIVE: Brachial plexus injuries are usually severe and involve the entire brachial plexus, sometimes occurring with root avulsions. Imaging and electrodiagnostic studies are an essential part of the lesion evaluation; however, the results sometimes show a discrepancy. The cutaneous silent period (SP) is a spinal inhibitory reflex mediated by small-diameter A-delta nociceptive fibers. The aim of the study was to determine if cutaneous SP testing may serve as a useful aid in evaluation of brachial plexus injury and/or in the diagnosis of root avulsion. METHODS: In 19 patients with traumatic brachial plexus injury (15 males, age 18-62 years) we performed a clinical examination, CT myelography and neurophysiological testing. A needle EMG was obtained from muscles supplied by C5-T1 myotomes. Cutaneous SP was recorded after painful stimuli were delivered to the thumb (C6 dermatome), middle (C7) and little (C8) fingers while subjects maintained voluntary contraction of intrinsic hand muscles. RESULTS: Electrodiagnostic and imaging studies confirmed root avulsion (partial or total) maximally involving C5, C6 roots in 12 patients, whereas only in 4 of them the cutaneous SP was partially absent. In the remaining subjects, the cutaneous SP was preserved. CONCLUSION: In brachial plexopathy even with plurisegmental root avulsion, the cutaneous SP was mostly preserved. This method cannot be recommended as a reliable test for diagnosis of single root avulsion; however, it can provide a quick physiological confirmation of functional afferent A-delta fibers through damaged roots and/or trunks. The clinicians may add this test to the diagnosis of spinal cord dysfunction.
Keywords: dospělí; Female; Cutaneous silent period; Brachial Plexus; reakční čas; Adult; ženské pohlaví; Reflex; svalová kontrakce; Adolescent; Brachial plexopathy; lidé; elektromyografie; plexus brachialis; Electromyography; Root avulsion; radikulopatie; Male; A-delta fibers; Radiculopathy; reflex; Reaction Time; neuropatie brachiálního plexu; lidé středního věku; mužské pohlaví; Muscle Contraction; Middle Aged; mladiství; Brachial Plexus Neuropathies; Humans